Preferência de umidade na oviposição de grilos de serrapilheira (orthoptera: grylloidea): experimentos de campo e laboratório - Martins, Fernando de Farias (2017)
For species that do not exhibit parental care such as oviparous insects, choosing a favorable oviposition site is of utmost importance for brood success. Niche theory predicts that crickets should show a bell-shaped oviposition response to substrate humidity. However, at least one lab experiment with mole crickets (Orthoptera: Gryllotalpoidea) indicated a linear oviposition responses to substrate humidity. The house cricket Acheta domesticus (Orthoptera: Grylloidea) also shows a linear juvenile body growth response to substrate humidity, which suggests a positive relationship between humidity and oviposition preference. We evaluated the relationship between oviposition frequency and substrate humidity in forest litter- dwelling species, primarily composed of Ubiquepuella telytokous, using field experiments. We also tested oviposition responses of U. telytokous to substrate humidity in a laboratory experiment. We offered oviposition substrates that varied in humidity from zero percent to maximum substrate water absorption capacity. Oviposition preference was estimated using presence or absence of eggs as a binary response variable, adjusted logistic regression (GAMM) was used to test for non-linear responses, and GLMs were used to test linear responses. We found that oviposition probability increased linearly with substrate humidity for U. telytokous in both field and lab experiments. Our results demonstrate the importance of substrate humidity as an ecological niche requirement for this species. This work bolsters knowledge of litter cricket life history association with humidity, and suggests that litter crickets may be particularly threatened by changes in climate that favor habitat drying.